Systematic analysis of the process of deodorization of vegetable oil with the presence of mobile nozzles - Naziraliyeva, Nigora; Xamdamov, Anvar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Plants from which oil is extracted include cotton, soybeans, sunflowers, peanuts, safflower, corn, olives, and sesame. Currently, the most common method for industrially extracting cottonseed oil is by pressing - extraction. In the production of cottonseed oil, about 20-22 kg of free fatty acids are released from one ton of black oil with an acid number of 4.2 mg KON. The main part of them is 95.2% during the chemical refining of "black oil", and the remaining 4.8% is separated during the deodorization process.